The effects of surface treatments on properties and corrosion protection of AZ91D magnesium alloy - Wan Zulkifli, Wan Amirul Shafiz (UTeM, 2018)
Magnesium alloy, especially AZ91D is extensively applied in the electronic industries due to its low densities, excellent strength to the weight ratio, and good electromagnetic shielding. However, its poor performance in a corrosive environment has restricted its applications. In this work, the corrosion resistance of the AZ91D surface was investigated by comparing three surface treatment techniques known as the oxidation, PA-PVD, and the duplex treatment. The treated AZ91D were analysed using varied methods, encompassing, microstructure analysis via SEM and optical microscope, phases analysis using XRD characterization, and surface roughness analysis using surface profilometer, to name a few. The results captured the occurrence of grain recrystallization, the elimination of twin boundaries on the grain structure of untreated AZ91D and the elimination Mg17Al12 phase precipitation after the oxidation process in which the Mg17Al12 precipitate is believed to accelerate the corrosion rate by acting as cathode near the Mg matrix. The presence of MgO phase after oxidation process and duplex treatment also has increased the corrosion resistance of AZ91D by the development of oxide passive film on the AZ91D surface. Cross-sectional SEM images show that the Cr2O3 coating has successfully been deposited on the AZ91D surface with 2μm thickness. Throughout the thorough analysis, the study has concluded that, the oxidized AZ91D has the best corrosion resistance, followed by the duplex treatment and PA-PVD process. Further recommendations are also proposed in this thesis.